(untitled) (Fiep Bulletin - online, 2015)
Physical Education at initial grades has been of concern for professionals since the end of the 1970’s, with the belief that specialist teachers should teach Physical Education classes for those grades. Since then, specialists and all-around teachers have shared the responsability for the work with Physical Education at initial grades. The aim of this paper was to analyse the professional schooling of the specialist teacher, as well as the all-around teacher, to work with Physical Education in those grades. The study was carried out in the city of Pelotas-RS: at the College level in a Magesterial Course, and the Undergraduate level in both a Pedagogy and a Physical Education Course. We started from the pressuposition that Physical Education at initial grades has to be understood in a wide range as well as being integrated to the curricular components of these grades. Thus, it is no longer viewed as an ancillary activity at the edge of others which from the curriculum, in order to be taken as a goal in itself. Take into account the qualitative nature of the study, we utilized the semistructural interview and the record analysis (curricular reports, adenda, course plans) as tools to investigate within these Courses what the instructional basis of the teacher is for his working with Physical Education at initial levels. Such investigation showed that the urgent need to start from a better quality of professional schooling of the Physical Education teacher in initial grades is a consensus in the Teaching Training Courses. This urgency, however, is not always translated into the attitudes of such professionals. The collected data point to the need of a better articulation among the contents worked out in the activities being part of the curricular plans of these Courses, as well as a need of a better understanding of the historical, social, political, economic, and pedagogical context in which Physical education is inserted.